Neuroprotective effects of Argon are mediated via an ERK‐1/2 dependent regulation of heme‐oxygenase‐1 in retinal ganglion cells. (27th April 2015) - Ulbrich, Felix; Kaufmann, Kai B.; Coburn, Mark; Lagrèze, Wolf Alexander; Roesslein, Martin; Biermann, Julia; Buerkle, Hartmut; Loop, Torsten; Goebel, Ulrich
Abstract Retinal ischemia and reperfusion injuries (R‐IRI) damage neuronal tissue permanently. Recently, we demonstrated that Argon exerts anti‐apoptotic and protective properties. The molecular mechanism remains unclear. We hypothesized that Argon inhalation exert neuroprotective effects in rats retinal ganglion cells (RGC) via an ERK‐1/2 dependent regulation of heat‐shock proteins. Inhalation of Argon (75 Vol%) was performed after R‐IRI on the rats′ left eyes for 1 h immediately or with delay. Retinal tissue was harvested after 24 h to analyze mRNA and protein expression of heat‐shock proteins −70, −90 and heme‐oxygenase‐1, mitogen‐activated protein kinases (p38, JNK, ERK‐1/2) and histological changes. To analyze ERK dependent effects, the ERK inhibitor PD98059 was applicated prior to Argon inhalation. RGC count was analyzed 7 days after injury. Statistics were performed using anova. Argon significantly reduced the R‐IRI‐affected heat‐shock protein expression (p < 0.05). While Argon significantly induced ERK‐1/2 expression (p < 0.001), inhibition of ERK‐1/2 before Argon inhalation resulted in significantly lower vital RGCs (p < 0.01) and increase in heme‐oxygenase‐1 (p < 0.05). R‐IRI‐induced RGC loss was reduced by Argon inhalation (p < 0.001). Immunohistochemistry suggested ERK‐1/2 activation in Müller cells. We conclude, that Argon treatment protects R‐IRI‐induced apoptotic loss of RGC via an ERK‐1/2 dependent regulation of heme‐oxygenase‐1. <boxed-text content-type="graphic" id="jnc13124-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We proposed the following possible mechanism for Argon‐mediated neuroprotection: Argon exerts its protective effects via an induction of an ERK with subsequent suppression of the heat shock response. In conclusion, ischemia and reperfusion injuries and subsequent neuronal apoptosis are attenuated. These novel findings may open up new opportunities for Argon as a therapeutic option, especially since Argon is not toxic.